Thermographic non-destructive inspection of wind turbine blades using unmanned aerial systems. (April 2015) - Galleguillos, C.; Zorrilla, A.; Jimenez, A.; Diaz, L.; Montiano, Á. L.; Barroso, M.; Viguria, A.; Lasagni, F.
Abstract : Wind turbines are gaining importance in the last years because of their high efficiency during energy production without greenhouse gas emission. Furthermore, they can be installed both on- and off-shore. However, wind blade maintenance operations have become difficult and expensive due basically to size aspects and operative costs related with their location and out-off service period. A non-destructive technique capable of detecting most significant in service defects in composite wind blade is infrared thermography (IRT). However, this method can only be applied by developing cost efficient in situ inspection strategies. This work presents a feasibility study for defect detection during maintenance operations in wind blades using unmanned aerial systems (UASs). IRT inspections are performed by means of passive IRT methodology first (i) for specimen located at the ground level with artificial defects (like delaminations, cracks, impact damage and debondings) and later (ii) during flight operation using an rotorcraft UAS. The developed inspection strategies, test results and several features of the developed acquisition system are reported.